2015
DOI: 10.1371/journal.pone.0117941
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperglycaemia on In Vitro Cytokine Production and Macrophage Infection with Mycobacterium tuberculosis

Abstract: Type 2 diabetes mellitus is an established risk factor for tuberculosis but the underlying mechanisms are largely unknown. We examined the effects of hyperglycaemia, a hallmark of diabetes, on the cytokine response to and macrophage infection with Mycobacterium tuberculosis. Increasing in vitro glucose concentrations from 5 to 25 mmol/L had marginal effects on cytokine production following stimulation of peripheral blood mononuclear cells (PBMCs) with M. tuberculosis lysate, LPS or Candida albicans, while 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
3
37
2
2
Order By: Relevance
“…We previously reported similar alterations in IL-1b and IL-10 through manipulation of the glycolytic enzyme PKM2 in TLR-stimulated murine BMDM (7). Our observations are supported by increased cytokine production in response to M. tuberculosis lysate in PBMC cultured in media with high glucose concentration (17). Although our results demonstrate that TNF-a production is not directly impacted by glycolytic reprogramming, IL-1b was shown to augment TNF-a signaling in M. tuberculosis infection (18); thus, glycolysis may also affect this cytokine indirectly at later time points.…”
Section: Discussionsupporting
confidence: 67%
“…We previously reported similar alterations in IL-1b and IL-10 through manipulation of the glycolytic enzyme PKM2 in TLR-stimulated murine BMDM (7). Our observations are supported by increased cytokine production in response to M. tuberculosis lysate in PBMC cultured in media with high glucose concentration (17). Although our results demonstrate that TNF-a production is not directly impacted by glycolytic reprogramming, IL-1b was shown to augment TNF-a signaling in M. tuberculosis infection (18); thus, glycolysis may also affect this cytokine indirectly at later time points.…”
Section: Discussionsupporting
confidence: 67%
“…Multiple in vitro studies have revealed that high glucose leads to increased expression of inflammatory cytokine genes in primary-derived or cell line-derived monocytes and macrophages [3638], as well as increased binding of monocytes to endothelial cells [37]. Importantly, although the transcriptional levels of proinflammatory mediators can be measured in cells exposed to high glucose levels [37], an actual increased secretion of inflammatory cytokines only becomes apparent after costimulation, e.g., with phorbol 12-myristate 13-acetate (PMA) [36], LPS or Mycobacterium tuberculosis [39, 40]. This suggests that glucose itself only ‘primes’ monocytes, by inducing (mild) changes in the transcriptional program, while a clear proinflammatory phenotype only evolves after costimulation with pathogenic stimuli.…”
Section: Hyperglycemia Associates With Monocyte Activation To Contribmentioning
confidence: 99%
“…Since IFN-gamma has been detected in human atherosclerotic plaques, it is accepted that IFN-gamma is a proatherogenic cytokine, and its action occurs through the activation of macrophages, with subsequent accumulation of lipids [63]. In disagreement with these studies, other studies have demonstrated that (i) severe hypercholesterolemia in mice decreases IFN-gamma response and induces IL-10 response [64]; (ii) PBMCs incubated in high glucose concentrations produced higher levels of TNF-alpha, IL-1beta, and IL-6, while IFN-gamma did not change [65]; (iii) studies with whole blood or PBMCs of T2D patients with and without tuberculosis reported decrease in IFN-gamma production [66–68]. Similarly, we found a negative correlation between the IFNG gene with glycemic and lipid profiles; furthermore, the patients with dyslipidemia (G1, G2, and G3) expressed lower IFNG mRNA levels than systemically healthy patients (G4 and G5).…”
Section: Discussionmentioning
confidence: 99%